Analysis and Research on NVH Problem of Double Clutch Transmission - Zhou Xinjian; Mao Le; Bao Guangzhen (Jixie chuandong)
The abnormal noise quality problem is measured in off-line detection of a DCT250 dual clutch transmission. The fault phenomena is analyzed by ABA testing. The results show that gear direction helix angle error of second gear on external input shaft is strongly related with the NVH problems. Through the verification of the machining process of tooth to crossover,it is confirmed that the center hole of the input shaft head is not concentric with the A datum,which is the root cause of the gear direction helix angle error. Combined with the results of the test and analysis,the problem of abnormal quality of the noise is solved by controlling the spline alignment and detecting the full tooth profile periodically. Finally,the correctness of the analysis and the feasibility of the optimal scheme are verified by the final trend tracking. The analysis method of test not only shortens the processing time of NVH problem,but also has good reference value for solving similar engineering problem.